2023
DOI: 10.3390/membranes13100846
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Physical, Chemical, and Structural Properties of Low- and High-Methoxyl Pectin-Based Film Matrices Including Sunflower Waxes

Mayra C. Chalapud,
Ma. de la Paz Salgado-Cruz,
Erica R. Baümler
et al.

Abstract: The development of bio-based materials remains one of the most important alternatives to plastic materials. Although research in this field is growing, reporting various materials and methodologies, it is still necessary to increase exploration. The aim of this work was to expand and complement previous research on the preparation and characterization of high- and low-methoxyl pectin films obtained by casting, with the addition of commercial and recovered sunflower waxes. The results showed that the addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 43 publications
0
0
0
Order By: Relevance
“…Referring to the results of research conducted by [3] regarding the Study of the Physical, Chemical, and Structural Properties of Low-and High-Methoxyl Pectin-Based Film Matrices Including Sunflower Waxes, it was concluded that regarding chemical characteristics, most of the raw materials' chemical groups were found in the resulting films, and the presence of C-H bending due to pectin gelation was observed. Finally, the compatibility and contribution of pectin and sunflower waxes to the production of the films were demonstrated, as well as the possibility of using materials from industrial waste in food packaging applications.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Referring to the results of research conducted by [3] regarding the Study of the Physical, Chemical, and Structural Properties of Low-and High-Methoxyl Pectin-Based Film Matrices Including Sunflower Waxes, it was concluded that regarding chemical characteristics, most of the raw materials' chemical groups were found in the resulting films, and the presence of C-H bending due to pectin gelation was observed. Finally, the compatibility and contribution of pectin and sunflower waxes to the production of the films were demonstrated, as well as the possibility of using materials from industrial waste in food packaging applications.…”
Section: Literature Reviewmentioning
confidence: 99%